THE EFFECT OF DISCOVERY LEARNING AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES PPKN SUBJECTS IN CLASS IV SDN 105316 BERANTI - Polintan Rehulina Sembiring; Reh Bungana Br.Perangin-Angin; Yakobus Ndona (Sensei International Journal of Education and Linguistic, 2021)
This study aims to determine: 1) The effect of discovery learning and conventional learning models on student learning outcomes, 2) The influence of learning motivation on student learning outcomes. 3) The interaction between learning models and learning motivation on student learning outcomes. This study used a quasi-experimental research method. The research was conducted from April to May 2021.The population of this study were the fourth grade students of SDN 105316 Beranti, the number of which was 42 students who were determined randomly by random sampling technique. The research sample was 22 students of class IVA as the experimental class and 22 students of IVB class as the control class. The data collection technique used a learning motivation questionnaire and a learning outcome test. The data analysis technique used two-way analysis of variance. The results of the study are as follows: (1) There are differences in learning outcomes students who are taught with a learning model discovery learning with an average value of 85,919 higher than the learning outcomes of students taught by the learning model conventional on average 80,000, the analysis of variance results show Fcount value of 4.333> Ftable value of 3.22 and a probability or significance value of 0.00 <0.05, so H0 is rejected, (2) There is a significant difference between student learning outcomes with high learning motivation and the average85.07and students who have low learning motivation on average 57.81. Result of analysis of variance obtained Fcount value of 79.45> Ftable value of 3.22 and a significant value of 0.013 <0.05, so that H0 is rejected., (3) There is an interaction between discovery learning model and student motivation in improving student PPKn learning outcomes, analysis of variance results Fcount value of 8.807> Ftable value of 3.22 and a significance of 0.014 <0.05, so that H0 is rejected.